Save the tree of life or get lost in the woods - Bourne Philip E (Biology Direct, 2010)
Abstract Background The wealth of prokaryotic genomic data available has revealed that the histories of many genes are inconsistent, leading some to question the value of the tree of life hypothesis. It has been argued that a tree-like representation requires suppressing too much information, and that a more pluralistic approach is necessary for understanding prokaryotic evolution. We argue that trees may still be a useful representation for evolutionary histories in light of new data. Results Genomic data alone can be highly misleading when trying to resolve the tree of life. We present evidence from protein abundance data sets that genomic conservation greatly underestimates functional conservation. Function follows more of a tree-like structure than genetic material, even in the presence of horizontal transfer. We argue that the tree of cells must be incorporated into any new synthesis in order to place horizontal transfers into their proper selective context. We also discuss the role data sources other than primary sequence can play in resolving the tree of cells. Conclusions The tree of life is alive, but not well. Construction of the tree of cells has been viewed as the end goal of the study of evolution, where in reality we need to consider it more of a starting point. We propose a duality where we must consider variation of genetic material in terms of networks and selection of cellular function in terms of trees. Otherwise one gets lost in the woods of neutral evolution. Reviewers This article was reviewed by Dr. Eric Bapteste, Dr. Arcady Mushegian, and Dr. Celine Brochier.